Positive Self-Talk on Pencak Silat Performances (Department of Physical Education, Sport, Health and Recreation, 2019)
Self-talk is basic mental training techniques for changing or influencing mind patterns that can be done in a closed manner so that they are not heard by others, or are open that can be heard by others and directed by oneself. The purpose of the present study was to test the effectiveness of a self-talk intervention on pencak silat performance (straight, sabit, and side kick). Participants were 30 athlete (M age 19 years). The method used in this study was a experiment method with 2 group (STQ Intervention vs. Control Group). The results of this study establish the effectiveness of self-talk in sport, encourage the use of self-talk as a strategy to enhance pencak silat performance.